Consensus clinical management guidelines for Niemann-Pick disease type C - Geberhiwot, Tarekegn; Moro, Alessandro; Dardis, Andrea; Ramaswami, Uma; Sirrs, Sandra; Marfa, Mercedes Pineda; Vanier, Marie T; Walterfang, Mark; Bolton, Shaun; Dawson, Charlotte; Héron, Bénédicte; Stampfer, Miriam; et al. (Orphanet journal of rare diseases, 2018)
Niemann-Pick Type C (NPC) is a progressive and life limiting autosomal recessive disorder caused by mutations in either the NPC1 or NPC2 gene. Mutations in these genes are associated with abnormal endosomal-lysosomal trafficking, resulting in the accumulation of multiple tissue specific lipids in the lysosomes. The clinical spectrum of NPC disease ranges from a neonatal rapidly progressive fatal disorder to an adult-onset chronic neurodegenerative disease. The age of onset of the first (beyond 3 months of life) neurological symptom may predict the severity of the disease and determines life expectancy.NPC has an estimated incidence of ~ 1: 100,000 and the rarity of the disease translate into misdiagnosis, delayed diagnosis and barriers to good care. For these reasons, we have developed clinical guidelines that define standard of care for NPC patients, foster shared care arrangements between expert centres and family physicians, and empower patients. The information contained in these guidelines was obtained through a systematic review of the literature and the experiences of the authors in their care of patients with NPC. We adopted the Appraisal of Guidelines for Research & Evaluation (AGREE II) system as method of choice for the guideline development process. We made a series of conclusive statements and scored them according to level of evidence, strengths of recommendations and expert opinions. These guidelines can inform care providers, care funders, patients and their carers of best practice of care for patients with NPC. In addition, these guidelines have identified gaps in the knowledge that must be filled by future research. It is anticipated that the implementation of these guidelines will lead to a step change in the quality of care for patients with NPC irrespective of their geographical location.
Keywords: Niemannova-Pickova nemoc typu C; Niemann-Pick Type C; Management; Guidelines; NPC; lidé; Practice Guidelines as Topic; Niemann-Pick Disease, Type C; Humans; Diagnosis; směrnice pro lékařskou praxi jako téma